Current progress of rehabilitative strategies in stem cell therapy for spinal cord injury: a review - Syoichi Tashiro (Nature Portfolio, 2021)
Abstract Stem cell-based regenerative therapy has opened an avenue for functional recovery of patients with spinal cord injury (SCI). Regenerative rehabilitation is attracting wide attention owing to its synergistic effects, feasibility, non-invasiveness, and diverse and systemic properties. In this review article, we summarize the features of rehabilitation, describe the mechanism of combinatorial treatment, and discuss regenerative rehabilitation in the context of SCI. Although conventional rehabilitative methods have commonly been implemented alone, especially in studies of acute-to-subacute SCI, the combinatorial effects of intensive and advanced methods, including various neurorehabilitative approaches, have also been reported. Separating the concept of combined rehabilitation from regenerative rehabilitation, we suggest that the main roles of regenerative rehabilitation can be categorized as conditioning/reconditioning, functional training, and physical exercise, all of which are indispensable for enhancing functional recovery achieved using stem cell therapies.